1996
DOI: 10.1002/j.1460-2075.1996.tb00794.x
|View full text |Cite
|
Sign up to set email alerts
|

DAG, a gene required for chloroplast differentiation and palisade development in Antirrhinum majus.

Abstract: We have identified a mutation at the DAG locus of Antirrhinum majus which blocks the development of chloroplasts to give white leaves with green revertant sectors. The green areas contain normal chloroplasts whereas the white areas have small plastids that resemble proplastids. The cotyledons of dark‐grown dag mutant seedlings have plastids which also resemble proplastids. The palisade cells in the white areas of dag mutant leaves also lack their characteristic columnar shape. The DAG locus was cloned by trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 54 publications
6
115
0
Order By: Relevance
“…The MS data indicated that the protein encoded by At3g15000 was the top candidate RARE1-interacting protein present in the immunoprepitate, because it had the largest number of matches of MS/MS spectra other than RARE1 (SI Appendix, Table S1). The gene encodes a member of the differentiation and greening (DAG) family; mutants in members of this gene family exhibit chloroplast biogenesis defects (32,33). Yeast two-hybrid analysis confirmed the interaction between RARE1 and the protein encoded by At3g15000, which was, therefore, named RIP1 (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The MS data indicated that the protein encoded by At3g15000 was the top candidate RARE1-interacting protein present in the immunoprepitate, because it had the largest number of matches of MS/MS spectra other than RARE1 (SI Appendix, Table S1). The gene encodes a member of the differentiation and greening (DAG) family; mutants in members of this gene family exhibit chloroplast biogenesis defects (32,33). Yeast two-hybrid analysis confirmed the interaction between RARE1 and the protein encoded by At3g15000, which was, therefore, named RIP1 (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Identification of this type of communication has come from an examination of a handful of nuclear gene-induced pigment mutants whose white leaf tissues have abnormal plastids and cells, and altered palisade and/or spongy mesophyll cell layer organizations. These include dag of Antirrhinum majus (Chatterjee et al, 1996), dcl of tomato (Keddie et al, 1996), and several Arabidopsis mutants, including cla1 (Mandel et al, 1996;Estévez et al, 2000), cue1 (Li et al, 1995;Streatfield et al, 1999), and pac (Reiter et al, 1994;Meurer et al, 1998). Because the products of the genes defined by these mutations reside in the plastid, it has been argued that these proteins are not independently required for plastid development and cell differentiation (and consequently for proper leaf morphogenesis), but that the effects on mesophyll cell differentiation are a consequence of incomplete chloroplast differentiation.…”
Section: Plastid-to-nucleus Communication Regulates Leaf Developmentmentioning
confidence: 99%
“…Up to 15 transgenic tobacco plants transformed with each construct under the control of the double CaMV 35S promoter were examined for the levels of the bZIP transcripts in leaves. Leaves from selected plants expressing high levels of each transgene were also examined for transcript levels of histone genes (H4) (Forbert et al, 1994) and members of the tobacco CAB gene family (Chatterjee et al, 1996) and the small subunit gene of Rubisco (RBCS), by probing RNA gel blots. Loading was quantified by probing with the rDNA from pea to identify ribosomal RNA and with a UBIQUITIN cDNA clone from Antirrhinum.…”
Section: Bzip910 and Bzip911 Can Alter Histone And Cab Transcript Levmentioning
confidence: 99%
“…Three independent transformants expressing bZIP910 with its 5Ј leader (910L) and without its 5Ј leader (910S), three independent transformants expressing bZIP911 with its 5Ј leader (911L) and one expressing bZIP911 without its 5Ј leader (911S) were compared to plants expressing bZIP910 and bZIP911 in antisense orientation (AS910 and AS911, respectively) and the average of two control plants transformed with vector alone (C). RNA gel blots were probed with genes encoding histone H4 (from Antirrhinum majus; a gift from John Doonan, Forbert et al, 1994), CAB (from tobacco; Chatterjee et al, 1996) and ubiquitin (from Antirrhinum majus). Transcript levels were quantified by phosphor imager and values were corrected for small variations in loading by standardization to the ubiquitin values.…”
Section: Bzip910 and Bzip911 Can Alter Histone And Cab Transcript Levmentioning
confidence: 99%